The degree of graduates of the Fourth Faculaty of Education in Quneitra managed to implement the Graphic Organizers (the strategy of the circular house as an Example) (Journal of Hama University, 2020)
The aim of the research was to find out the degree to which the graduate of the Fourth Faculaty of Education in Quneitra managed to implement the Graphic Organizers (example  the strategy of the circular house). the researcher followed the analytical descriptive method, the study was conducted on a sample of (28) graduates  they teach in government schools in Quneitra governorate. The research tools included A list of the circular house strategy procedures, steps ,and a note card that included (39) basic procedures in three stages of the circular house strategy. The research reached the following results:     1- The degree of graduates' ability to the strategy of the circular house in general came to a (medium) extent. As to the degree to which they can take each of the three steps, the results showed that the performance step came first and the degree of ability was( great), while the design step came in second place and the degree of mastery was (to a moderate degree) and the step of the meditation was in the third place and (to a small degree).     2- There are no differences of statistical significance at the level of significance (0.05) between the average grades of graduates according to variable type of secondary certificate (scientific/ literary).    3-There are differences of statistical significance at a level of significance (0.05) between the average grades of graduates according to variable type of experience, and these differences for the benefit of teachers, whose experience was three year’s experience.